THE INFLUENCE OF TRADITION ON DEGRADATION OF ENVIRONMENTAL ETHICS VALUES - SOBCZYK, Wiktoria; BIEDRAWA, Agnieszka; FILIPIAK, Agnieszka (Trends in education, 2008)
The article describes the examples of the influence of the tradition in selected countries on biological life devastation. Breaking environmental law and bestiality in animals treating are also observed in the so-called civilized nations of Europe and North America.
Keywords: traditions; ethics; ecology